Effective cure cycle development via flow optimization and advanced cure environments - D. Kim (Taylor & Francis Group, 2020)
Out-time and moisture absorption in prepregs are generally unavoidable in an industrial setting, where prepreg layup can take weeks. The resin cross-linking and viscosity increase that occurs during out-time can reduce resin flow during a specified cure cycle, causing porosity. In this study, a flow-optimized cure cycle was developed, leveraging both flow level and time during out-of-autoclave (OoA) processing. First, predictive cure kinetics and viscosity models were used to model viscosity evolution under selected cure conditions, accounting for initial out-times and humidity conditioning. To quantify resin flow, an ‘effective flow number’ metric was defined as the integration of inverse viscosity evolution until the resin gelation point. The method described revealed that a rapid heating rate achieved by use of advanced tooling was essential to achieve a high effective flow number. The experimental results showed that the effective flow number is a useful criterion to limit flow-induced defects. The method presented also extends the boundary (by 175%) of the manufacturer’s specified out-life for OoA prepreg materials.